“In the early Anthropocene”: Witnessing Environmental Emergency in Kathleen Jamie’s Essays - Monika SZUBA (E-REA)
The spectre of the Anthropocene haunts Kathleen Jamie’s Surfacing (2019). Already appearing in the opening paragraph of the first essay, the term announces the presence of some other time, marking an ambiguous temporality of things past and things yet to come. It is there in the rapidly eroding coastline that, on the one hand, reveals material traces of a long-lost culture, and on the other, disrupts human lives and augurs an imminent threat of cultural discontinuity. Bearing witness to environmental emergency, Jamie avoids solastalgic representations, revealing layers of inapparent meanings. An immediate consequence of climate breakdown epitomised in tundra fires, melting permafrost and rising sea levels, ecosystem distress coalesces with positive social processes as a damaged culture becomes revitalised. The essay focuses on the discussion of the representation of climate crisis, and that which surfaces, or emerges in its wake, and how it effects irreversible change. It proposes to examine Jamie’s depiction of loss and resilience that is both melancholic and hopeful, where grief blends with expectation of renewal, reverberating in the image of the Bering Sea merging with the American continent. Finally, it aims to explore the language of Surfacing, which records environmental emergency and witnesses its consequences to the non-human as well as human world.